ENANTIOSPECIFIC SYNTHESIS OF SWAINSONINE, (1S, 2R, 8R, 8AR)-1,2,8-TRIHYDROXYOCTAHYDROINDOLIZINE, FROM D-MANNOSE - Fleet, G; Gough, M; Smith, P (1984)
An enantiospecific synthesis of swainsonine from D-mannose is described; the heterocyclic rings of swainsonine are constructed by two intramolecular reductive aminations caused by the catalytic hydrogenation of an azidoaldehyde with 5 equivalents of hydrogen. © 1984.